A novel 2D MTMHM based key generation for enhanced security in medical image communication - C. Sivaranjani Devi; Rengarajan Amirtharajan (Scientific Reports)
Abstract In today’s tech-driven world, secure communication of medical information is a critical necessity. Protecting the patient’s sensitive medical data through encryption algorithms based on chaos theory has emerged as a prominent research trend. This research proposes a novel 2D-Modified Tinkerbell Map with Henon Map (2D-MTMHM) chaotic equation to generate the pseudo-random key sequences for medical image encryption. Combining the Tinkerbell map with the Henon map exhibits a broader range of chaotic behaviour, making it highly suitable for cryptographic applications. The nature, randomness and sensitivity of the developed 2D-MTMHM equation are validated through the NIST SP800-22 statistical test, bifurcation diagram, Lyapunov exponent, permutation entropy, attractor trajectory, sample entropy and sensitivity test. The generated random key sequences trigger the proposed medical image encryption algorithm, which integrates a shuffling-diffusion process. The shuffling unit of the proposed medical image encryption scheme consists of three distinct phases: row-wise shuffling, column-wise shuffling, and selective shuffling based on cut-off points. The diffusion unit is designed to bit-wise scramble the pixel-shuffled image, further enhancing the randomness and security of the encrypted image. Simulation and experimental analysis demonstrate that the encryption system effectively resists statistical, differential and Brute-force attacks. The algorithm achieves an average entropy of 7.99, a correlation coefficient nearer to zero, a Number of Pixels Change Ratio (NPCR) of 99.6%, and a Unified Average Changing Intensity (UACI) of 33.4%. A larger key space of 10270 is obtained, implying that the algorithm provides security against brute−force attacks.